Pengaruh Komunikasi Kerja, Komitmen Organisasional, Dan Konflik Kerja Terhadap Kinerja Pegawai Dinas Pendidikan Dan Kebudayaan Kota Probolinggo - Wulandari, Wahyu Putri; Ngatimun, Ngatimun; Pujiastuti, Agustina (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research was conducted at the Office of Education and Culture in Probolinggo City with the aim of knowing the significant influence of the variables of work communication, organizational commitment, and work conflict partially and simultaneously on employee performance at the Office of Education and Culture in Probolinggo City. The type of research used is quantitative research with a causal associative approach. Data collection techniques with interviews, questionnaires, and documentation. The population referred to in this study were all employees at the Probolinggo City Education and Culture Office. Sample determination was carried out using non-probability sampling which determined a sample of 60 respondents. This research data uses primary and secondary data. The data analysis techniques used are validity test, reliability test, classical assumption test, multiple regression analysis, coefficient of determination analysis and hypothesis testing The results showed that work communication has a significant effect on employee performance, organizational commitment has a significant effect on performance, and work conflict has a significant effect on employee performance.